Evaluation of Functional and Radiological Outcome of Five-Pin Technique in Management of Distal End Radius Fractures - Mahendra Solanki; Dev Krishan Sharma; Rakesh Prasad; Mitul Jain (Journal of Orthopedics, Traumatology and Rehabilitation, 2022)
Introduction: Distal end radius fractures are the most common fractures of the upper extremity. The most common mode of injury is a fall on outstretched hand. Closed reduction and percutaneous pinning with “the five-pin technique” improve the reliability of fixation. The current study aimed to assess the clinical and functional outcome of fixation of distal radius fractures using the five-pin technique.